THE ROLE OF MATERIALISM BETWEEN SOCIAL COMPARISON & IMPULSE BUYING: Peran Materialism Diantara Social Comparison & Impulse Buying - Ayang Pradila; Astri Yuza Sari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Impulse buying occurs when various features such as flash sales, free shipping, and promotional notifications on Shopee often encourage consumers to make spontaneous purchases without careful consideration, thus potentially giving rise to consumptive behavior and waste.This study aims to analyze the effect of social comparison on impulsive buying with the mediating role of materialism. In this study, a sample of 220 was used which was then processed using the Smart PLS 3 application to test the hypothesis. The results showed that 1) social comparison had a positive and significant effect on Materialism, 2) social comparison did not have a positive and significant effect on Impulse Buying, 3) Materialism had a positive and significant effect on Impulse Buying, 4) social comparison had a positive and significant effect on Impulse Buying mediated by Materialism